Anterior and Rotational Knee Laxity Does Not Affect Patient-Reported Knee Function 2 Years After Anterior Cruciate Ligament Reconstruction. Issue 9 (July 2019) - Magnussen, Robert; Reinke, Emily K.; Huston, Laura J.; Andrish, Jack T.; Cox, Charles L.; Dunn, Warren R.; Flanigan, David C.; Hewett, Timothy; Jones, Morgan H.; Kaeding, Christopher C.; Lorring, Dawn; et al.
Background: While a primary goal of anterior cruciate ligament (ACL) reconstruction is to reduce pathologically increased anterior and rotational knee laxity, the relationship between knee laxity after ACL reconstruction and patient-reported knee function remains unclear. Hypothesis: There would be no significant correlation between the degree of residual anterior and rotational knee laxity and patient-reported outcomes (PROs) 2 years after primary ACL reconstruction. Study Design: Cross-sectional study; Level of evidence, 3. Methods: From a prospective multicenter nested cohort of patients, 433 patients younger than 36 years of age injured in sports with no history of concomitant ligament surgery, revision ACL surgery, or surgery of the contralateral knee were identified and evaluated at a minimum 2 years after primary ACL reconstruction. Each patient underwent Lachman and pivot-shift evaluation as well as a KT-1000 arthrometer assessment along with Knee injury and Osteoarthritis Outcome Score and subjective International Knee Documentation Committee (IKDC) scores. A proportional odds logistic regression model was used to predict each 2-year PRO score, controlling for preoperative score, age, sex, body mass index, smoking, Marx activity score, education, subsequent surgery, meniscal and cartilage status, graft type, and range of motion asymmetry. Measures of knee laxity were independently added to each model to determine correlation with PROs. Results: Side-to-side manual Lachman differences were IKDC A in 246 (57%) patients, IKDC B in 183 (42%) patients, and IKDC C in 4 (<1%) patients. Pivot-shift was classified as IKDC A in 209 (48%) patients, IKDC B in 183 (42%) patients, and IKDC C in 11 (2.5%) patients. The mean side-to-side KT-1000 difference was 2.0 ± 2.6 mm. No significant correlations were noted between pivot-shift or anterior tibial translation as assessed by Lachman or KT-1000 and any PRO. All predicted differences in PROs based on IKDC A versus B pivot-shift and anterior tibial translation were less than 4 points. Conclusion: Neither the presence of IKDC A versus B pivot-shift nor increased anterior tibial translation of up to 6 mm is associated with clinically relevant decreases in PROs 2 years after ACL reconstruction.